From exclusion to optional participation: Fathers in books on childcare 1846–2010 - Gíslason, Ingólfur V. (Menntavísindasvið Háskóla Íslands, 2018)
One of the major issues in a gendered world concerns the relationship of men and women towards children, mainly their roles as a father or a mother. This has for a long time been a major diving factor in Western societies and Iceland is no exception. But these roles have changed dramatically in the last centuries as the more general social roles of men and women (and children) have changed. At the same time the general discourse has changed and acted on the social structures surrounding parenthood. The article examines this discourse as it is presented in books and booklets published in Iceland from 1846 to 2010, focusing on pregnancy, birth and the caretaking of infants. All in all 37 books and booklets were read and content analysis used to examine how the role of the father is portrayed. Three major periods can be detected. The first and the longest, spans from the first book in 1846 up to the nineteen-sixties. During this period the father is more or less absent. Several sources make no mention of a father at all and in other cases he is mentioned once or twice as a “provider” or a handyman. However, towards the end of the period his role has begun to increase. The second period is from the nineteen-sixties up to the final decade of the twentieth century. This is a period of major social change, mainly in the roles of women. Mothers enter the labour market, the educational revolution of women really takes off and they become visible in all areas traditionally dominated by men. And there is also one important change regarding fathers. It is during this period that fathers begin to be present at the birth of their children, something that very soon becomes the norm. In the books of this period the father is much more visible, but mainly as mother’s “helper” or assistant. He rarely does anything without being asked. And, furthermore, he is clumsy in his dealings with the child (and the mother) and has little idea about what is going on. But more and more he is present and it is emphasised that he, and his ...